Pengaruh Fasilitas Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Puskesmas Mambi - Insani, J Fuji; Ratna, Ratna (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
The Mambi Health Center is one of the first-level health service facilities that plays an important role in the national health system with a working area consisting of 2 sub-districts and 11 villages namely Mambi Sub-District, Sendana Village Sondonglayuk Village, Bujungmanurung Village, Tapalinna Village, Talipukki Sub-District, Rantebulahan Village, Saludurian Village , Salualo Village, Salumaka Village, Pamoseang Village, Salubanua Village and Indobanua Village. In its activities, the Mambi Health Center faces a number of problems related to employee performance that is not optimal, which is allegedly the result of inadequate work facilities available and low employee discipline. This study aims to determine the effect of work facilities and work discipline on employee performance at the Mambi Health Center. The research method used is a quantitative method with primary data obtained using a questionnaire. The population is all employees of the Mambi Health Center and a sample of 38 people with proportional random sampling. The data analysis method used is validity test, reliability test, multiple linear regression analysis and hypothesis testing t test and f test. The results showed that work facilities and work discipline had a partial and simultaneous effect on the performance of Mambi Health Center employees.